A BCR-ABL1 cutoff of 1.5% at 3 months, determined by the GeneXpert system, predicts an optimal response in patients with chronic myeloid leukemia. - Valentín García-Gutiérrez; María T Gómez-Casares; José M Puerta; Juan M Alonso-Domínguez; Santiago Osorio; Juan C Hernández-Boluda; Rosa Collado; María J Ramírez; Fátima Ibáñez; María L Martín; Juan D Rodríguez-Gambarte; Carolina Martínez-Laperche; et al. (PLoS ONE, 2017)
In chronic myeloid leukemia (CML) patients, 3-month BCR-ABL1 levels have consistently been correlated with further outcomes. Monitoring molecular responses in CML using the GeneXpert (Cepheid) platform has shown an optimal correlation with standardized RQ-PCR (IS) when measuring BCR-ABL1 levels lower than 10%, as it is not accurate for values over 10%. The aim of the present study was to determine the predictive molecular value at three months on different outcome variables using the Xpert BCR-ABL1 MonitorTM assay (Xpert BCR-ABL1). We monitored 125 newly diagnosed consecutive CML patients in the chronic phase (CML-CP) using an automated method: Xpert BCR-ABL1. Only 5% of patients did not achieve an optimal response at 3 months, and the 10% BCR-ABL1 cutoff defined by RQ-PCR (IS) methods was unable to identify significant differences in the probabilities of achieving a complete cytogenetic response (CCyR) (50% vs. 87%, p = 0.1) or a major molecular response (MMR) (60% vs. 80%, p = 0.29) by 12 months. In contrast, a cutoff of 1.5% more accurately identified differences in the probabilities of achieving CCyR (98% vs. 54%, p<0.001) and MMR (88% vs. 56%, p<0.001) by 12 months, as well as probabilities of treatment changes (p = 0.005). Therefore, when using the Xpert BCR-ABL1 assay, a cutoff of 1.5% at 3 months could with high probability identify patients able to achieve an optimal response at 12 months.